The Needs–Affordances–Features Perspective for the Use of Social Media1 - Karahanna, Elena; Xu, Sean Xin; Xu, Yan; Zhang, Nan (Andy) (MIS Quarterly, 2018)
The paper develops a needs–affordances–features (NAF) perspective on social media use which posits that individuals’ psychological needs motivate their use of social media applications to the extent to which these applications provide affordances that satisfy these needs. Our theoretical development builds upon two psychological theories, namely self-determination and psychological ownership, to identify five psychological needs (needs for autonomy, relatedness, competence, having a place, and self-identity), that we posit are particularly pertinent to social media use. According to NAF, these psychological needs will motivate use of those social media applications that provide salient affordances to fulfill these needs. We identify such affordances through a comprehensive review of the literature and of social media applications and put forth propositions that map the affordances to the psychological needs that they fulfill. Our theory development generates important implications. First, it has implications for social media research in that it provides an overarching comprehensive framework for the affordances of social media as a whole and the related psychological needs that motivate their use. Future studies can leverage NAF to identify psychological needs motivating the use of specific social media sites based on the affordances the sites provide, and design science research can leverage NAF in the design and bundling of specific social media features to engage users. Second, it has implications for technology acceptance research in that NAF can enrich existing models by opening up the mechanisms through which psychological needs influence user perceptions of social media and their use patterns and behaviors. Finally, NAF provides a new lens and common vocabulary for future studies, which we hope can stimulate cumulative research endeavors to develop a comprehensive framework of information systems affordances in general and the psychological needs that information systems satisfy.